(untitled) (Zia e Tahqeeq, 2025)
Arab women have participated in the poetic movement during early period of Islam particularly under the Umayyads and the Abbasids. Their contribution is considerably comparable with what of the Arab women played in pre-Islamic era. Al-Khansa is considered one of significant poetess during the early period of Islam. This study aims to analyze the works of leading poetess of early period particularly Sakina bint Hussayn and Bathnah bint Hibba al-Azriya. This paper also highlights the contribution of Arab women in the field of eloquence and rhetoric. It has also been observed that Arab poetess were significantly inspired by the Quranic themes and benefited greatly from them.